Technical Note:Curve fitting, for: T type thermocouple Copper-constamtine - Zewar, Sardar (Sulaimani Journal for Pure and Applied Sciences, 1999)
An empirical formula has been obtained mathematically to be used in determination of temperature, which is dtermined from the thermocouple output for (T) type (Copper - Constantan).